Obtención del proceso tecnológico de nuggets a partir de Chaetobranchus flavescens (bujurqui) con alto valor nutricional - Escobar Rengifo, Jean Paul Alexander (2022)
The Peruvian Amazon has countless hydrobiological species that have been poorly studied, for this reason it was of great interest to carry out the project with a little commercialized species to give it added value and enhance its nutrients; the type of research was a completely randomized experimental design with a quantitative approach where the study factors were F1= Nuggets formulation and F2= Starch with three levels with 9 treatments and 27 experiments for the preparation of bujurqui nuggets, where it was determined by rule out the choice of only 3 treatments, having as a criterion the crocodile texture presented by the treatments. The flowchart was applied to obtain Nuggets from Chaetobranchus flavescens (bujurqui). To evaluate the nutritional quality of the 3 treatments, physicochemical analyzes were carried out by means of which the final product was determined, obtaining a percentage of: 20.96% carbohydrates, 6.87% fat, 17.01% protein, 52.16% humidity, 6.30% fiber, 3.00% ash, 213.7 kcal, 5.30 pH, 1.83% acid value, 5.52% peroxide value. In addition, the final product according to the Peruvian technical standard indicates that it is within the established parameters by which it was determined that the product is safe and suitable for human consumption and has a stability of 30 days from its production; therefore, the present technology can be used by any company interested in increasing nutritional values.